Sem medo das palavras: Introdução à Obra de Lourdes Ramalho - Ferreira, Jefferson Nunes (2011)
This dissertation is a brief introduction to the work of one of the most important playwriters of the present time: Lourdes Ramalho (Maria de Lourdes Nunes Ramalho, Jardim do Seridó- RN, 1926). Her literary production for adults (plays and cordéis ) has been thought here considering three aspects that, connected, give to her writing a singular form: the archetypicals images and characters of the european Middle Ages imaginary and of the Northeast of Brazil, the regionalist discourse based on folk culture and the medieval iberian focus on brazilian northeastern culture. At the same time, those marks put the author among a large literary tradition that, during the XXth century, tried to find a cultural identity to the brazilian Northeast. There is also, in this study, a attempt to approach the author style to the grotesque realism of François Rabelais, bringing up the analysis of this author and style made by the Literature theoretician Mikhail Bakhtin. After that, there is a discussion about the theatrical language and it is shown how two of Lourdes Ramalho s plays ( As Velhas and Romance do conquistador ) were brought to the stage through the interpretations of those texts made by one of the most creative directors of contemporary theatre: Moncho Rodriguez (Vigo/Spain, 1951). Those stagings of Lourdes Ramalho s texts become stronger the idea of a brazilian Northeast still immersed into traditions and esthetics that go back to the iberian Middle Ages. Both of the artists see, imaginate and create a brazilian Northeast as a space of traditions (iberians, jewishes, moorishes, africans) and also as an universe where the presence of the supernatural, of the fantastic, is very strong.